Ketogenic Diet and Epilepsy: What We Know So Far - D’Andrea Meira, Isabella; Romão, Tayla Taynan; Pires do Prado, Henrique Jannuzzelli; Krüger, Lia Theophilo; Pires, Maria Elisa Paiva; da Conceição, Priscila Oliveira (Frontiers in Neuroscience, 2019)
The Ketogenic Diet (KD) is a modality of treatment used since the 1920s as a treatment for intractable epilepsy. It has been proposed as a dietary treatment that would produce similar benefits to fasting, which is already recorded in the Hippocratic collection. The KD has a high fat content (90%) and low protein and carbohydrate. Evidence shows that KD and its variants are a good alternative for non-surgical pharmacoresistant patients with epilepsy of any age, taking into account that the type of diet should be designed individually and that less-restrictive and more-palatable diets are usually better options for adults and adolescents. This review discusses the ketogenic diet, including the possible mechanisms of action, applicability, side effects, and evidence for its efficacy, and for the more-palatable diets such as the Modified Atkins Diet (MAD) and the Low Glycemic Index Diet (LGID) in children and adults.